Mineralization of sulfonamides from wastewater using ozone-based systems - T. H. Ho; C. H. Wu; T. Y. Han; W. J. Syu (Water Science and Technology, 2021)
Ozone, UV/ozone, ozone/persulfate (PS) and UV/ozone/PS systems were used to mineralize sulfonamides. Sulfadiazine (SDZ), sulfamerazine (SMR) and sulfamethazine (SMZ) were the target compounds. The novel contribution of this study is its determination of the effects of PS addition, sulfonamide structure, pH and salinity on sulfonamide mineralization in ozone-based systems. The mineralization rate of sulfonamides satisfied pseudo-first-order kinetics. The SMZ mineralization rate constant in ozone, UV/ozone, ozone/PS and UV/ozone/PS systems at pH 5 were 0.0058; 0.0101; 0.0069 and 0.0802 min−1, respectively, and those at pH 7 were 0.0075; 0.0116; 0.0083 and 0.0873 min−1, respectively. The increase in the number of methyl substituents in the heterocyclic group of SMZ and the corresponding increase in the steric hindrance of radical addition, reduced mineralization rates below those of SMR and SDZ. The addition of PS promoted sulfonamide mineralization in the ozone-based systems; conversely, salinity inhibited sulfonamide mineralization. HIGHLIGHTS Ozone, UV/ozone, ozone/PS and UV/ozone/PS systems were investigated.; The mineralization constants of SDZ, SMR and SMZ were compared.; The effects of pH, salinity and PS addition on mineralization were determined.; SMZ was most refractory and UV/ozone/PS was most effective.;